Are Psychological Treatments for Adults With Histories of Violent Offending Associated With Change in Dynamic Risk Factors? A Meta-Analysis of Intermediate Treatment Outcomes - Papalia, Nina (Criminal justice and behavior, 2020)
This meta-analysis examined whether psychological treatments delivered to adults with histories of violent offending in correctional and forensic mental health settings were related to change in dynamic risk factors. Twenty-two controlled studies (86% comprised male samples) were identified via a comprehensive search. Treatments had a significant effect overall, with small to moderate improvements in trait anger, social problem solving, impulsivity, and general social skill. The treatment effect for antisocial cognitions was nonsignificant. There were a small number of significant moderators, which provide preliminary indications of treatment features that may promote greater change. However, small sample sizes and difficulties disentangling moderating effects preclude drawing firm conclusions. While these results are useful and promising, the field remains limited by few high-quality outcome studies, disparate outcome/measure selection, inconsistent/incomplete reporting of evaluations, and limited information about whether change in dynamic risk factors predicts reductions in recidivism. Suggestions for advancing the field are provided.